تنمر الزوج ضد المرأة العاملة و انعكاساته على التنشئة الاجتماعية للأبناء من منظور الأمهات العاملات دراسة ميدانية بمديرية الشباب و الرياضة بمدينة تبسة - حافي, فاطمة; بوشامة, باديس (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة إلى التعرف إلى مظاهر تنمر الزوج في الأسرة الجزائرية وانعكاساته على التنشئة الاجتماعية للأبناء، للأمهات العاملات بمديرية الشباب والرياضة لولاية تبسة ، عددهن20عاملة، حيث وزعت إستبانة عدد فقراتها(28) فقرة مقسمة إلى خمس مجالات والاعتماد على برنامج برنامج spss للمعاجلة الإحصائية، حيث بلغت الفا كرومباخ 0.87 للتعرف إلى نتائج الدراسة فقد تم استخدام سلم ليكرت الثلاثي، لمعرفة درجة الأثر، وبينت الدراسة عدة نتائج أهمها: يتنمر الزوج بأشكال متعددة ضد المرأة العاملة، كما يؤثر ذلك على العلاقات الأسرية بدرجة متوسطة (العزلة الاجتماعية، التوتر، الارتياح في المنزل، الانتقاد، التقليل من مجهود الأم) ويؤثر على سلوكيات الأبناء بدرجة متوسطة(اكتساب سلوك التنمر، إظهار ردود أفعال حيال التنمر) Abstract: The study aimed to identify the manifestations of the husband’s bullying in the Algerian family and its repercussions on the social upbringing of children, for working mothers in the Directorate of Youth and Sports of the state of Tebessa, whose number is 20 workers, where the number of its paragraphs (28) was distributed, divided into five areas and dependence on the spss program for statistical treatment, which reached Krumbach's alpha 0.87 to identify the results of the study, the triple Likert scale was used, to find out the degree of impact, and the study showed several results, the most important of which are: The husband bullies in multiple forms against the working woman. It also affects family relationships to a moderate degree (social isolation, stress, comfort at home, criticism, underestimating the mother’s effort) and affects the behavior of children to a moderate degree (acquiring bullying behavior, showing reactions to bullying).
Husband bullying against working women and its repercussions on the social upbringing of children from the perspective of working mothers, a field study in the Directorate of Youth and Sports in Tebessa
مقال
Keywords: التنشئة الاجتماعية، التنمر، المرأة العاملة; working woman, husband bullying, social